Advances in CRISPR/Cas9-Based Gene Editing in Filamentous Fungi - Bin Ma; Yimiao Li; Tinghui Wang; Dongming Li; Shuang Jia (Journal of Fungi)
As an important class of microorganisms, filamentous fungi have crucial roles in protein secretion, secondary metabolite production and environmental pollution control. However, characteristics such as apical growth, heterokaryon, low homologous recombination (HR) efficiency and the scarcity of genetic markers mean that the application of traditional gene editing technology in filamentous fungi faces great challenges. The introduction of the RNA-mediated CRISPR/Cas (clustered regularly interspaced short palindromic repeat/CRlSPR-associated protein) system in filamentous fungi in recent years has revolutionized gene editing in filamentous fungi. In addition, the continuously expressed CRISPR system has significantly improved the editing efficiency, while the optimized sgRNA design and reduced cas9 concentration have effectively reduced the off-target effect, further enhancing the safety and reliability of the technology. In this review, we systematically analyze the molecular mechanism and regulatory factors of CRISPR/Cas9, focus on the optimization of its expression system and the improvement of the transformation efficiency in filamentous fungi, and reveal the core regulatory roles of HR and non-homologous end-joining (NHEJ) pathways in gene editing. Based on the analysis of various filamentous fungi applications, this review reveals the outstanding advantages of CRISPR/Cas9 in the enhancement of protein secretion, addresses the reconstruction of secondary metabolic pathways and pollutant degradation in the past decade, and provides a theoretical basis and practical guidance for the optimization of the technology and engineering applications.